2014
DOI: 10.1016/j.jaac.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Frontal–Striatal–Thalamic Circuit White Matter Development in Pediatric Obsessive-Compulsive Disorder

Abstract: Objective Atypical development of frontal-striatal-thalamic circuitry (FSTC) has been hypothesized to underlie the early course of obsessive-compulsive disorder (OCD); however, the development of FSTC white matter tracts remains to be studied in young patients. Method To address this gap, we scanned 36 patients with pediatric OCD compared to 27 healthy controls, aged 8 to 19 years, with diffusion tensor imaging (DTI) to measure fractional anisotropy (FA), an index of white matter coherence. Tract-based spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…However, we did find some evidence implicating the splenium as well, suggesting a possibly more general role for the corpus callosum in these emerging behaviors. Though less often the focus of such studies, there is precedence for corpus callosum involvement with RRBs associated with ASD [ 5 ] and other psychiatric conditions [ 72 , 73 ]. There is also the strong possibility that our findings reflect biobehavioral mechanisms specific to early development.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did find some evidence implicating the splenium as well, suggesting a possibly more general role for the corpus callosum in these emerging behaviors. Though less often the focus of such studies, there is precedence for corpus callosum involvement with RRBs associated with ASD [ 5 ] and other psychiatric conditions [ 72 , 73 ]. There is also the strong possibility that our findings reflect biobehavioral mechanisms specific to early development.…”
Section: Discussionmentioning
confidence: 99%
“…The flow chart of the identification and attrition of studies is provided in Figure 1. There were 20 TBSS studies included in the review (six studies recruiting child/adolescent patients (Ameis et al., 2016; Fitzgerald et al., 2014; Jayarajan et al., 2012; Rosso et al., 2014; Silk et al., 2013; Zarei et al., 2011) and 14 studies with adult patients (Benedetti et al., 2013; Bollettini et al., 2018; Bora et al., 2011; Fan, van den Heuvel, et al., 2015; Fontenelle et al., 2011; Gan et al., 2017; Hartmann et al., 2016; Hawco et al., 2017; Magioncalda et al., 2016; Nakamae et al., 2011; Salles Andrade et al., 2019; Spalletta et al., 2014; Yagi et al., 2017; Zhou et al., 2018)). Demographic information and clinical characteristics of participants in all 20 TBSS studies, as well as scanning parameters and main findings of FA analyses, are shown in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the 20 studies, peak coordinates of FA alteration could not be retrieved after contacting the authors in three studies (Bora et al., 2011; Fontenelle et al., 2011; Hartmann et al., 2016), and one study conducted statistical comparisons with parametric t tests in Statistical Parametric Mapping software (Spalletta et al., 2014). Therefore, 16 studies met criteria to be included in the present meta‐analysis (six studies recruiting child/adolescent patients (Ameis et al., 2016; Fitzgerald et al., 2014; Jayarajan et al., 2012; Rosso et al., 2014; Silk et al., 2013; Zarei et al., 2011) and 10 studies with adult patients (Benedetti et al., 2013; Bollettini et al., 2018; Fan, van den Heuvel, et al., 2015; Gan et al., 2017; Hawco et al., 2017; Magioncalda et al., 2016; Nakamae et al., 2011; Salles Andrade et al., 2019; Yagi et al., 2017; Zhou et al., 2018). No study used overlapping patient samples.…”
Section: Resultsmentioning
confidence: 99%
“…Although our findings also implicate connections between frontal and cingulate regions, our methodology was indeed different and applied to an unmedicated sample. Other findings have been mixed, indicating either greater FA across the brain (Zarei et al, 2011), including the corpus callosum, cingulum and other tracts (Gruner et al, 2012), lower FA (Rosso et al, 2013) or less white matter volume (Chen et al, 2013) in cingulate, callosal and other regions, or no differences (Fitzgerald et al, 2014;Jayarajan et al, 2012;Silk et al, 2013) compared with healthy youth. These prior studies typically examined small sample sizes (8-36 patients) with most taking psychiatric medications and/or exhibiting psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…ENIGMA highlighted larger thalamic volumes (Boedhoe et al, 2017b), but no significant differences in cortical thickness (Boedhoe et al, 2017a) in unmedicated youth with OCD compared with healthy participants. Diffusion MRI findings examining white matter structure have been mixed, identifying either no differences (Fitzgerald et al, 2014;Jayarajan et al, 2012;Silk et al, 2013), greater (Gruner et al, 2012;Zarei et al, 2011) or lower fractional anisotropy (FA) (Lazaro et al, 2014a;Rosso et al, 2013), or lower white matter volume (Chen et al, 2013;Lazaro et al, 2014b) in pediatric OCD across mainly corpus callosum, frontal, and cingulate areas. One pediatric study suggested that caudate volume predicts response to group CBT or pharmacotherapy (Vattimo et al, 2019), but no study, to our knowledge, has assessed brain structure or structural connectivity as predictors of individual CBT in unmediated pediatric OCD.…”
Section: Introductionmentioning
confidence: 99%